2023
DOI: 10.1021/acsestwater.2c00384
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Perfluorinated Alkyl Acid Uptake Rates by a Tube Passive Sampler in Water

Abstract: Per- and polyfluoroalkyl substances (PFAS) are a group of 4000+ man-made compounds of great concern due to their environmental ubiquity and adverse effects. Despite general interest, few reliable detection tools for integrative passive sampling of PFAS in water are available. A microporous polyethylene tube with a hydrophilic–lipophilic balance sorbent could serve as a flow-resistant passive sampler for PFAS. The tube’s sampling rate, R s, was predicted based on either partitioning and diffusion or solely diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(42 citation statements)
references
References 46 publications
9
33
0
Order By: Relevance
“…However, our previous work showed that sorption is clearly a large factor that requires further experimentation before more complex models can be fully validated. 2 The time-dependent approach outlined in Booij et al seems to be in good agreement with our time-independent approach. 1 The modeling work proposed in Dunn et al…”
supporting
confidence: 86%
See 4 more Smart Citations
“…However, our previous work showed that sorption is clearly a large factor that requires further experimentation before more complex models can be fully validated. 2 The time-dependent approach outlined in Booij et al seems to be in good agreement with our time-independent approach. 1 The modeling work proposed in Dunn et al…”
supporting
confidence: 86%
“…2 The time-dependent approach outlined in Booij et al seems to be in good agreement with our time-independent approach. 1 The modeling work proposed in Dunn et al…”
supporting
confidence: 86%
See 3 more Smart Citations